Structural Analysis of the Pasar Minggu Subdistrict Health Center Building in South Jakarta City - Ahmad Difky Nur Fathoni; Syahrul UIIa AI Muarif; Tira Roesdiana (Riviera Publishing, 2026)
In light of the rising incidence of natural disasters, it is crucial to ensure that all buildings, particularly those serving public functions, are capable of withstanding a range of potential loads. This study examines the structural integrity of the Pasar Minggu Subdistrict Health Center in South Jakarta through analysis using ETABS software, deriving internal forces from the facility's working drawings in alignment with the requirements of SNI 2847:2019, SNI 1726:2019, and SNI 1727:2020. Employing a quantitative methodology via ETABS V18.1.1, the analysis incorporates primary data gathered from on-site measurements alongside secondary data sourced from relevant literature and established design standards. Key steps encompass structural modeling, load determination, and an assessment of the capacity of critical components, including columns, beams, and slabs. The findings indicate that the majority of the building's structural elements satisfy the prescribed strength criteria. Nonetheless, columns K4 on the Dak floor and K6 on the Dak staircase and terrace at the first-floor level fall short of the Weak Beam-Column Strength (SBLB) requirements, underscoring the necessity for targeted design enhancements and reinforcement measures. These outcomes underscore the value of thorough structural evaluations in architectural planning. The study further offers guidance on refinements to bolster the structure's safety and longevity, while stressing adherence to prevailing regulations in infrastructure projects.